Thermogravimetric and thermochemical studies of Malaysian oil palm shell waste - Hussain, Ahmad; Ani, Farid Nasir; Darus, Amer Nordin; Ahmed, Zainal (Penerbit UTM Press, 2006)
Recently, owing to environmental and economic considerations, interest in utilizing biomass for the production of energy and chemicals is increasing. Palm oil shell wastes are one of the main agriculture waste in Malaysia. Pyrolysis is one of the most promising thermochemical techniques for recovering energy from biomass. Pyrolysis of oil-palm shell waste was first carried out using thermogravimetric analysis (TGA). The effects of heating rate on the pyrolytic properties were investigated. The kinetic parameters have also been determined using integral method. This paper also describes the experimental results from a bench-scale circulating fluidized-bed (CFB) test rig, installed at SIRIM Berhad, Shah Alam, suitable for gasification and combustion experiments using different biomass materials. The purpose of the tests was to investigate the suitability of the selected fuels for energy production using Circulating Fluidised Bed Combustor (CFBC) while taking care of the flue gas emissions. Operating parameters (such as temperature, type of biomass, feeding rate, heating rate, pressure, primary air and reactor configuration) are believed to influence significantly the pyrolysis of a biomass. Temperature is one of the most important operating variants so the experimental studies were done to investigate the influence of temperature on pyrolysis. the concentrations of CO, NOx and CO2 in the flue gas were measured. The combustion performances were evaluated by varying the primary gas flow through the CFBC tubular furnace. the emission of NOx ranged from 38–75 ppm while the CO emissions were high for higher primary air flow rates.